Spontaneous Aching Pain and Peculiar Involuntary Movements: A Case Report of Painful Legs and Moving Toes and Review of the Literature - Yang-yi Fan; Yan Xu; Xu-guang Gao (Case Reports in Medicine)
Painful legs and moving toes (PLMT) is a rare syndrome characterized by spontaneous neuropathic pain and peculiar involuntary movements in the lower limbs, especially the toes and feet. As it is a relatively rare disorder worldwide, the exact pathophysiology still remains a mystery. Until recently, numerous methods of clinical treatments have been tried; however, the success rate of the therapies is still very low. Here, we report a case of PLMT and also summarize the recent clinical and research literatures regarding clinical presentation, electrophysiological features, etiology, treatment methods, and prognosis of this disorder. Doctors should be aware of this rare syndrome in a patient with painful and/or restless legs. On the other hand, multiple clinical treatments should be tried, even those which usually produce a poor outcome.